1990
DOI: 10.1007/bf01325216
|View full text |Cite
|
Sign up to set email alerts
|

Windows of vulnerability: Identifying critical age, gender, and racial differences predictive of risk for violent deaths in childhood and adolescence

Abstract: An analysis of national data was completed to assess historical trends in age differences regarding incidents of accidental, homicidal, and suicidal deaths of children and adolescents. Analyses were completed on data for 1979 and 1984 examining gender × age and race × age differences using raw frequencies, ratios of death to size of living cohort, and percentage of a given form of death to all deaths. Historical trends reveal a general decline in incidents of the three leading external causes of death. Males w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Prior studies suggested that adolescence is a particularly vulnerable period in terms of adjustment (Irwin, 1987;Adams et al, 1990). Accordingly, understanding and monitoring adolescents' HRQOL may facilitate researchers and clinical practitioners to help adolescents with acute and/or chronic dysfunctions following a stress event or treatment, long-term survivors with emerging problems, and individuals who are at risk for developing psychological difficulties (Mulhern et al, 1989;Eiser, 1995;Eiser and Morse, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Prior studies suggested that adolescence is a particularly vulnerable period in terms of adjustment (Irwin, 1987;Adams et al, 1990). Accordingly, understanding and monitoring adolescents' HRQOL may facilitate researchers and clinical practitioners to help adolescents with acute and/or chronic dysfunctions following a stress event or treatment, long-term survivors with emerging problems, and individuals who are at risk for developing psychological difficulties (Mulhern et al, 1989;Eiser, 1995;Eiser and Morse, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Adolescence also is often viewed as a stage with heightened risk for future development (Adams et al 1994;Gullotta and Adams 2005). Previous studies have suggested that adolescence is a particularly vulnerable period in terms of psychological adjustment (Adams et al 1990;Irwin 1987;Johnston et al 1988). Erikson (1953Erikson ( , 1968 postulated that identity formation is the main developmental task during adolescence.…”
Section: Features Of Self-identity In Adolescencementioning
confidence: 97%